2019
DOI: 10.11628/ksppe.2019.22.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Agro-Healing Activity Program on the Physiological Condition of Adults with Chronic Metabolic Diseases

Abstract: This study was conducted to find out the effects of agro-healing activities and strolling on the physiological conditions of patients with chronic metabolic diseases. A total of 11 subjects participated in agro-healing activities, and their average age was 49.6±11.3. Changes in their salivary cortisol were compared and analyzed before and after participating in the agro-healing activity program, and it was found that the stress hormone decreased after participating in the program. Differences in brain wave bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
4
5
0
Order By: Relevance
“…The high satisfaction of participants can be attributed to the content of the program designed according to the characteristics and environment of the healing farm. This result was similar to the result of Jang, Yoo, et al (2019) Note. 5-point Likert scale was used for the survey (N=18).…”
Section: Satisfaction Of Participants In Agro-healing Activities Withsupporting
confidence: 91%
See 1 more Smart Citation
“…The high satisfaction of participants can be attributed to the content of the program designed according to the characteristics and environment of the healing farm. This result was similar to the result of Jang, Yoo, et al (2019) Note. 5-point Likert scale was used for the survey (N=18).…”
Section: Satisfaction Of Participants In Agro-healing Activities Withsupporting
confidence: 91%
“…These studies support the result of this study that the stress level of participants was reduced after participating in agro-healing activities. Jang, Yoo, et al (2019) also reported that the ratio of alpha to high beta (RAHB) was measured to be high in most points after participating in agro-healing activities and that the ratio was high in T3 (temporal lobe) in charge of motor functions and O2 (occipital lobe) in charge of visual functions, which indicates that the activities are effective for stabilization and relaxation and supports the results of this study.…”
Section: Changes In the Cortisol Level Of Participants After Participsupporting
confidence: 86%
“…The fact that 5 out of 20 participants in the study have at least three chronic diseases, and that hypertension takes up the highest portion, represents the issue of the many diseases that the elderly participants have. Therefore, physical activities related to horticultural plants that use the five senses of humans such as plowing the soil, sowing seeds, watering plants and removing weeds (Matsuo and Miyajima, 1998) reduce depression or stress of the elderly with dementia or the elderly living in an institution (Kim, 2009;Kim, 2013), and reduce blood pressure and pulses (Jang et al, 2019), which support the usefulness of the agro-healing program in this study.…”
Section: Satisfaction Of Participants In the Program And Number Of Chsupporting
confidence: 62%
“…Agro-healing activities that utilize plants and nature as a medium were reported to be effective in improving children and adolescents' self-efficacy, psychological wellbeing, self-esteem and sociality and for increasing psychological and emotional relaxation such as reducing aggression, stress and depression (Kang et al, 2012;Keum, 2014;Park and Kim, 2010;Shin, 2010;Soga et al, 2017;Yun and Yoo, 2011). They were also reported to have positive effects on the mental health of adults such as reducing their depression and stress and to be helpful in maintaining their physical health by reducing blood pressure (Jang, Gim, et al, 2019;Jang, Yoo, et al, 2019), and to have other various effects such as improving the mental health of the elderly by reducing a sense of loneliness, depression and stress, improving cognitive functions, the performance of daily life activities and life satisfaction (Kang and Back, 2017;Kim and Yoo, 2010;Lee and Sim, 2004;Oh and Yoo, 2010;Yoo and Jeong, 2010). Seol et al (2019) proved that activities of producing and selling horticultural products were effective for the vocational rehabilitation of those with mental disorders, and You and Shin (2019) reported that forest experiences can promote the visual perception of children with mental disabilities.…”
Section: Introductionmentioning
confidence: 99%